Everybody Sells, But Who Wins? Winning Strategy in Channel Management at Ankur Seeds Ltd. - Arumugasamy, Velsamy; P, Karthikeyan (IIUM Journal of Case Studies in Management, 2019)
Marketing channels are set of interdependent organizations participating in the process of making a product or service available for use or consumption. They are the set of pathways a product or service follows after production, culminating in purchase and consumption by the final end user (Anne T Coughlan et al., 2007). Channel members earn margins that account for 30 percent to 50 percent of the ultimate selling price. Today’s successful companies typically employ multichannel marketing, using two or more marketing channels to reach customers in one market area. This case shows how Venu Abhiram, the Marketing Officer of Ankur Seeds Ltd., used different types of channel in the various geographical region of Rajasthan in India to market hybrid cotton seed. We can understand how he reduced channel conflict and successfully managed with push and pull marketing strategy. Apart from elaborating the channel system, this case highlights, gray market operation and the best part of the case was how Venu understood multiple reasons for gray market and created a win-win situation. This case brings in all necessary inputs to discuss the traditional channel system prevailing in Indian Rural markets.